The Administrative Flexibility of The Iraqi National Olympic Committee from Administrative Bureau Members’ point Of View in Sport Federations - Radhi, Haider; Wahaab, Salah (Journal of Physical Education, 2023)
The researchers aimed at constructing a scale for administrative flexibility in the Iraqi national Olympic committee as well as identifying this flexibility in the Iraqi international Olympic committee from the administrative bureau’s point of view in sport federations. They used the descriptive method on (210) members from (26) sport federation from the Iraqi national federations. The researchers applied Likert’s scale to form the scale that consisted of five statements (fully agree, agree, neither agree nor disagree, disagree, and fully disagree). The scale consisted of 20 statements applied on the subjects to conclude that the Iraqi national Olympic federation’s work should be flexibly in setting goals and strategic planning and that the programs set by the Iraqi national Olympic committee are not based on clear future plans to achieve perfect administration in sport federations.